Meltwater Channels on West Slope of Tug Hill Plateau, New York - Muller, E. H.; D. H. Cadwell (Northeastern Geology, 1994)
Underfit valleys, dry channels and channel reaches anomalously deflected to the southwest (oblique to the regional slope) characterize the western descent from the cuestaform Tug Hill Plateau in northern New York. These vestiges of glacial meltwater drainage potentially bear useful information regarding the nature and history of Late Wisconsinan ice sheet withdrawal from northern New York uplands. A key to this information lies in examination of modern glacial meltwater streams adjacent to glaciers such as Burroughs and Bering Glaciers in central southern Alaska. Draining from ice onto reversely sloping terrain, they are diverted into ephemeral and shifting ice-marginal reaches that persist only until deglaciation opens new routes on lower terrain. Successive diversions during continuing glacial retreat produce flights of horseshoe- or comma-shaped channels recording the history of glacial retreat. Interpreted in terms of their modern analogs, the vestiges of glaciomarginal meltwater drainage record a history of century or two of steady retreat following the Port Huron Advance during which meltwater penetrated this stagnating and increasingly debris-covered margin during ice sheet withdrawal from the Tug Hill. No evidence of catastrophic "megaflooding" is seen in this record.
Keywords: channels; drainage patterns; geomorphology; glaciers; glaciohydrology; hydrology; melt water; meltwater; New York; tributaries; Tug Hill Plateau